E-Servqual Digitalization Of Islamic Banks And Customer Retention In Surakarta - Annastya Ayu Pramesty; Budi Sukardi (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
This study aims to determine the effect of banking digitalization service quality on customer loyalty of Islamic banks in Surakarta city. This type of research is quantitative research with a sample of 100 bank customers who use Islamic bank digital services, using primary data obtained through direct distribution of a questionnaire with a Likert scale, the data is processed using multiple linear regression analysis. The research proves that efficiency, reliability, fulfillment, privacy, responsiveness has no significant effect on customer retention in using bank digital services, as evidenced by the statistical value of each variable, namely 0.763, 0.727, 0.083, 0.225, 0.093 greater than 0.05. Contact has a positive and significant effect on customer retention in the use of digital banking services with a statistical value of 0.012 less than 0.05. This research has implications for strengthening strategies and services in the use of digital FinTech by Islamic banks in Indonesia